The Reassessment of CAPM Relative Accuracy Comparative Study with Actual Price Movement in Indonesian (2019-2022) - Fajarini, Nurfahma; Heikal, Jerry (International Journal of Management and Business Applied, 2024)
This study aims to investigate the accuracy of the Capital Asset Pricing Model (CAPM) in predicting stock returns on the Indonesian Stock Exchange (IDX) during the period of 2019 to 2022. The objectives of the research are to benefit the individuals and communities such as enhancing individuals’ decision-making in predicting stock returns, advancing community understanding of financial markets, and contributing new investment insight for societal benefits. The sample comprises 45 selected stocks out of more than 700 stocks, using K-Means Clustering to ensure a diverse and representative dataset. The study compared CAPM’s predictions with the Moving Average (MA) method. Findings show CAPM’s decisions align 87% with MA-analyzed price movements, underscoring CAPM’s effectiveness and the value of using multiple methods for financial predictions. While CAPM proves robust during economic recovery, further analysis is needed for optimal investment strategies. This study’s results challenge some arguments against CAPM’s accuracy.